CHARACTERISTICS OF ENTREPRENEURSHIP, COOPERATIVE PRINCIPLES, THEIR INFLUENCE ON THE PERFORMANCE OF COOPERATIVE MANAGEMENT IN BANYUMAS, CENTRAL JAVA, INDONESIA - Akhmad Darmawan; Ahmad Zainal Abidin bin Abd Razak; Hariyaty Binti Ab Wahab (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to analyze and obtain empirical evidence regarding the influence of leadership, courage to take risks, innovation, voluntary and open membership, democratic member control, member economic participation, autonomy and freedom, education; training; information and cooperation among cooperatives on performance. Management of Cooperatives in Banyumas, Central Java, Indonesia. The method used is Multiple Linear Regression Analysis with analysis techniques F test, R2 test, and t test. Based on the results of testing and discussion, the results of innovation, democratic control by members, autonomy and freedom, education; training; information and cooperation among cooperatives affect the performance of cooperative administrators in Banyumas, Central Java, Indonesia. Meanwhile, Leadership, Courage to Take Risks, Voluntary and Open Membership, and Member Economic Participation do not affect the Performance of Cooperative Managers in Banyumas, Central Java, Indonesia. Keywords: Leadership, Courage to Take Risks, Innovation, Voluntary Membership and Openness, Control by Members in a democratic manner, Member Economic Participation, Autonomy and Freedom, Education; Training; Information, and Cooperation among Cooperatives